Effectiveness of UV sanitization of vegetables using polymerase chain reaction and microbial culture techniques - Adutwumwaah, Abena (2016)
A Thesis submitted to the Department of Biochemistry and Biotechnology College of Science in partial fulfillment of the requirements for the award of MSc degree in Biotechnology,